2021
DOI: 10.1029/2021ja029258
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Unusual Chorus Elements by Van Allen Probes

Abstract: Chorus waves are naturally occurring electromagnetic emissions in the magnetosphere, with the frequency typically falling into two distinct bands: the upper band (0.5f ce < f < 0.8f ce ) and the lower band (0.1f ce < f < 0.5f ce ) with a power gap near 0.5f ce (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 70 publications
3
10
0
Order By: Relevance
“…Liu et al. (2021) have shown by using Van Allen Probes that the initial frequency of distinct falling‐tone subpackets gradually increases, and the sequence of the initial part of subpackets is aligned as upper‐band rising‐tone emissions. The present result shown in Figure 11a5 is similar to the observation result by Liu et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al. (2021) have shown by using Van Allen Probes that the initial frequency of distinct falling‐tone subpackets gradually increases, and the sequence of the initial part of subpackets is aligned as upper‐band rising‐tone emissions. The present result shown in Figure 11a5 is similar to the observation result by Liu et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the case with ω p = 2.0Ω e , falling-tone emissions are generated from rising-tone emissions with the frequency range from 0.5Ω e to 0.7Ω e , which is upper-band chorus emissions. Liu et al (2021) have shown by using Van Allen Probes that the initial frequency of distinct falling-tone subpackets gradually increases, and the sequence of the initial part of subpackets is aligned as upper-band rising-tone emissions. The present result shown in Figure 11a5 is similar to the observation result by Liu et al (2021), except for the frequency gap between lowerband and upper-band chorus emissions.…”
Section: Dynamic Frequency Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of interactions between whistler‐mode waves and electrons is strongly determined by wave properties, and one of them is the wave normal angle (WNA; Ni et al., 2011; Shprits & Ni, 2009; Verkhoglyadova et al., 2010). In the Earth's magnetosphere, both quasi‐parallel (WNA0.17em<0.17em45° $\,< \,45{}^{\circ}$) (Burton & Holzer, 1974; Goldstein & Tsurutani, 1984; Li et al., 2011, 2013; Tsurutani et al., 2020) and oblique (WNA 0.17em>0.17em45° $\, > \,45{}^{\circ}$) (Agapitov et al., 2013; Gao et al., 2016; Li et al., 2011, 2013; Liu et al., 2021; Mourenas et al., 2014) whistler‐mode waves have been widely observed. Although quasi‐parallel whistler‐mode waves typically have the much larger magnetic amplitudes (Li et al., 2011), previous studies pointed out oblique whistler‐mode waves play a crucial role in electron dynamics as well as quasi‐parallel waves (Artemyev, Agapitov, et al., 2015, 2016; Li et al., 2014; Mourenas et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…• Using 7-year Van Allen Probe-A data, we have statistically studied oblique whistler-mode waves in the Earth's magnetosphere • Most of oblique waves are poleward propagating and their favored magnetic latitudes increase with magnetic local time, supporting propagation effect as the main cause • There also exist some equatorward propagating oblique waves confined within 𝐴𝐴 5 ° in the midnight sector, which may be locally excited Liu et al, 2021;Mourenas et al, 2014) whistler-mode waves have been widely observed. Although quasi-parallel whistler-mode waves typically have the much larger magnetic amplitudes (Li et al, 2011), previous studies pointed out oblique whistler-mode waves play a crucial role in electron dynamics as well as quasi-parallel waves (Artemyev, Agapitov, et al, 2015Li et al, 2014;Mourenas et al, 2012).…”
mentioning
confidence: 99%